Android-based Calorie Counting Monitoring Application Using Accelerometer Sensor - Erliwati, Erliwati; Juliandri, Dona; Yudithia, Frenzi Agres; Sandella, Rani Wilda (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2024)
The rapid evolution of wearable health monitoring technology, especially in the domain of calorie counting devices, underscores a notable advancement in integrating sensors with wireless communication for real-time health tracking. This study evaluates the design and performance of an Android-based calorie counting device that combines the MPU6050 accelerometer with the Wemos ESP8266 module. This integration is pivotal for delivering accurate caloric expenditure measurements. Testing revealed that the device operates with a high level of precision, achieving an average voltage measurement accuracy of 97.15%. Specifically, the battery voltage measured at 3.99V DC falls comfortably within the acceptable range of 3.7V DC to 4.2V DC. The TP4056 charger module, Wemos D1 R1 Mini, and MPU6050 accelerometer all maintained consistent voltages of 4.9V DC, aligning with their specified ranges. This consistency in voltage measurements indicates that the device components function within their designed parameters. Additionally, the device’s effective integration with the Blynk app significantly enhances its functionality. Users can input personal details such as age and step length into the app, which then accurately computes and displays the calories burned. This seamless interaction between hardware and software demonstrates the device’s capability to provide real-time health data effectively. Overall, the device exhibits reliable operation and precise performance, validating its design and confirming its successful operation within the anticipated parameters. This advancement contributes to the growing field of wearable technology by offering users a robust tool for health monitoring